Different measures of vulnerability in their relation to different dimensions of fear of crime - Killias, Martin (The British journal of criminology, 2000)
Vulnerability has, in research conducted over the last decade, been found to be significantly related to fear of crime. It seems to be particularly helpful in explaining seemingly disproportionate fear levels among women and the elderly, as well as in a few situational contexts. In the present research, a representative sample of Switzerland's population (N=726) was interviewed on various aspects of fear of crime in the public sphere. All respondents were asked how they assessed their own ability to escape or resist in case of an attack by a young assailant. In addition, interviewers rated several aspects of respondents' visible' vulnerability. In multivariate analyses, vulnerability, as assessed by respondents themselves, explained fears and worries about crime better than interviewer-assessed measures of vulnerability. It is concluded that, in comparison to demographic and contextual (neighbourhood) variables, physical vulnerability seems to play an important and consistent role in the genesis of fear of crime